Char particle emissivity of two coal chars in oxy-fuel atmospheres. (1st November 2016) - Graeser, P.; Schiemann, M.
Abstract: A newly designed experimental setup for the "in-flight" measurement of the emissivity of burning char particles in the spectral range from 1.25 μm to 5.5 μm is presented. Single coal particles (Colombian bituminous coal and Rhenish lignite) were burned in a flat flame burner under oxy-fuel conditions. As the spectral region from 850 nm to 2.5 μm is dominant for the radiative heat flux at temperatures typical for pulverized fuel combustion, the emissivity is measured spectrally resolved in this region by a fiber spectrometer. Additionally the total emissivity in the range from 2.4 μm to 5.5 μm is measured by an InSb-detector. As particle temperature and diameter are necessary for the experimental determination of the emissivity, two-color pyrometry with simultaneous particle size measurement was carried out in the visible wave length range. There are differences between the emissivities of both coal chars. These initial results represent the first emissivity measurements of pulverized coal char particles under combustion conditions.